A New Norisoprenoid and Other Compounds from Fuzhuan Brick Tea - Luo Zhen-mei; Tie-Jun Ling; Lixiang Li; Zhengzhu Zhang; Hongtao Zhu; Ying‐Jun Zhang; Xiaochun Wan (2012)
Fuzhuan brick tea, a kind of dark tea consumed mainly in the border regions of Southwestern and Northwestern China since the 1860s, is produced from the leaves of Camellia sinensis var. sinensis by microbial fermentation. From this special fermented tea, a new norisoprenoid, 3R,9R-oxido-5-megastigmene, was isolated, together with α-linolenic acid, strictin, isovitexin, astragalin, (+)-catechin, (-)-epicatechin, (-)-epicatechin gallate, (+)-gallocatechin, (-)-epigallocatechin, (-)-epigallocatechin gallate and gallic acid. The structures of the compounds were identified by spectroscopic means. The new compound didn't show any inhibition activity against the tested enteric pathogenic microorganisms at a concentration of 800 μg/mL by the hole plate diffusion method.